2019
DOI: 10.1155/2019/1925243
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Antagonists Reduce the Risk of Cardiovascular Mortality in Dialysis Patients: A Meta-Analysis

Abstract: Background and Purpose. Cardiovascular disease is the major cause of death in dialysis patients. Although aldosterone antagonists were considered a treatment for severe heart failure patients to reduce cardiac mortality, whether treating patients undergoing maintenance dialysis with aldosterone antagonists could reduce the risk of cardiocerebrovascular (CCV) remains unclear. We aim to systematically assess the efficacy and tolerability of the addition of aldosterone antagonists to conventional therapy in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Aldosterone breakthrough is accompanied by lower plasma renin activity (PRA), which is expressed as a rise in the aldosterone-to-renin ratio (more than 3 ng/dL per ng/mL/h) and reflects the volume expansion caused by aldosterone [ 63 , 64 ]. Several studies have shown that in CKD, the non-selective MRAs (spironolactone or eplerenone), when given on top of ACEi or ARBs, reduce proteinuria but increase potassium levels, and these agents may be beneficial in dialysis patients [ 65 , 66 , 67 ]. However, a small trial in dialysis patients showed no benefit [ 68 ].…”
Section: Medical Treatment Of Hf In Ckdmentioning
confidence: 99%
“…Aldosterone breakthrough is accompanied by lower plasma renin activity (PRA), which is expressed as a rise in the aldosterone-to-renin ratio (more than 3 ng/dL per ng/mL/h) and reflects the volume expansion caused by aldosterone [ 63 , 64 ]. Several studies have shown that in CKD, the non-selective MRAs (spironolactone or eplerenone), when given on top of ACEi or ARBs, reduce proteinuria but increase potassium levels, and these agents may be beneficial in dialysis patients [ 65 , 66 , 67 ]. However, a small trial in dialysis patients showed no benefit [ 68 ].…”
Section: Medical Treatment Of Hf In Ckdmentioning
confidence: 99%
“…En pacientes con terapia dialítica, el estudio DOHAS (Dialysis outcomes heart failure aldactone study) (22) analizó a 309 sujetos en hemodiálisis, con 25 mg/día de espironolactona vs. terapia convencional, observándose una reducción de la mortalidad o ingreso por eventos cardiovasculares en el grupo de espironolactona (HR 0,40 con IC del 95 %, 0,20-0,80; p valor = 0,017). Un 1,9 % del grupo de espironolactona presentó hiperkalemia severa y 10,2 % ginecomastia o mastodinia, en otros 2 metaanálisis tuvieron resultados semejantes (23,24). Actualmente se encuentran en marcha dos ensayos clínicos para tener más claridad en este grupo de pacientes, el ALCHEMIST (Aldosterone antagonist chronic hemodyalisis interventional survival trial) y el ACHIEVE (Aldosterone blockade for health improvement evaluation in end-stage renal disease) (6).…”
Section: Antagonistas Esteroideos Selectivos Del Receptor De Mineralo...unclassified
“…Flevari et al ( 9 ) found significant increased sodium potassium level and decreased blood pressure after MRAs treatment, while Lin et al ( 10 ) and Gross et al ( 11 ) suggested unchanged serum potassium and blood pressure, respectively. Previous meta-analyses have been limited by small number of clinical trials ( 12 ) or results for single system ( 13 ). Thus, spironolactone is not widely understood in subjects undergoing dialysis.…”
Section: Introductionmentioning
confidence: 99%